Participation Analysis of Fish Farmers in Fisheries Counseling Programs (Case Study: Ujung Loe District, Bulukumba Regency, South Sulawesi Province) - Tajuddin, Tajuddin (AgriSains, 2019)
This study aims to measure the level of community participation in fisheries extension activities, and understand the relationship between internal and external factors on the level of participation of fish farmers in fishery extension activities in Ujung Loe District, Bulukumba Regency. The method used is a survey method and rapid assessment through the interview process. The results obtained indicate that the level of participation of fish farmers in fishery extension activities in Ujung Loe District is at a good level, while internal and external factors both have a significant influence on the level of participation of fish farmers in each variable of fisheries extension conducted in Ujung Loe District, Bulukumba Regency.        Keyword: Communication, Participation, Assessment, Counseling, Social.